Pandemic potential of highly pathogenic avian influenza clade 2.3.4.4 A(H5) viruses. (5th March 2020) - Yamaji, Reina; Saad, Magdi D.; Davis, Charles T.; Swayne, David E.; Wang, Dayan; Wong, Frank Y.K.; McCauley, John W.; Peiris, J.S. Malik; Webby, Richard J.; Fouchier, Ron A.M.; Kawaoka, Yoshihiro; Zhang, Wenqing
Summary: The panzootic caused by A/goose/Guangdong/1/96‐lineage highly pathogenic avian influenza (HPAI) A(H5) viruses has occurred in multiple waves since 1996. From 2013 onwards, clade 2.3.4.4 viruses of subtypes A(H5N2), A(H5N6), and A(H5N8) emerged to cause panzootic waves of unprecedented magnitude among avian species accompanied by severe losses to the poultry industry around the world. Clade 2.3.4.4 A(H5) viruses have expanded in distinct geographical and evolutionary pathways likely via long distance migratory bird dispersal onto several continents and by poultry trade among neighboring countries. Coupled with regional circulation, the viruses have evolved further by reassorting with local viruses. As of February 2019, there have been 23 cases of humans infected with clade 2.3.4.4 H5N6 viruses, 16 (70%) of which had fatal outcomes. To date, no HPAI A(H5) virus has caused sustainable human‐to‐human transmission. However, due to the lack of population immunity in humans and ongoing evolution of the virus, there is a continuing risk that clade 2.3.4.4 A(H5) viruses could cause an influenza pandemic if the ability to transmit efficiently among humans was gained. Therefore, multisectoral collaborations among the animal, environmental, and public health sectors are essential to conduct risk assessments and develop countermeasures to prevent disease and to control spread. In this article, we describe an assessment of the likelihood of clade 2.3.4.4 A(H5) viruses gaining human‐to‐human transmissibility and impact on human health should such human‐to‐human transmission occur. This structured analysis assessed properties of the virus, attributes of the human population, and ecology and epidemiology of these viruses in animal hosts.